The Combined Measurement of Pelvic Organ Mobility and Hiatus Area Improves the Sensitivity of Transperineal Ultrasound When Detecting Pelvic Organ Prolapse - Wen, Xiaoduo; Tian, Haiyan; Yan, Xiaojing; Sun, Quiqing; Du, Yuanyuan; Wen, Denggui; Yang, Yi (Frontiers in Medicine, 2021)
Objective: To evaluate if combining measurement of levator hiatus area and pelvic organ mobility improves the sensitivity of transperineal ultrasound diagnosis (Index test) of pelvic floor prolapse (POP). Methods: Women consecutively examined in a tertiary gynaecological centre for symptoms of lower urinary tract and/or POP between January 2017 and June 2018 were prospectively recruited, after excluding those having a previous hysterectomy or corrective surgery. All subjects underwent a standardized interview, POP-Q (reference standard for patients and controls), and ultrasound measurement of Levator hiatus area at rest (rHA), on contraction (cHA), on Valsalva (vHA), and mobility of bladder neck (BNM), cervix (CM) and rectum ampulla (RAM). Receiver operating characteristic (ROC) curve analyses were performed to determine cut-off values for diagnosis. Diagnostic performance was assessed by sensitivity, specificity, and area under curve (AUC). Results: A total of 343 women were eligible for analysis, including 247 prolapse ( stage 2-3) and 96 controls. POP cases have significantly larger rHA, vHA, cHA,BNM, CM , and RAM than controls. Each parameter discriminates POP and controls significantly in ROC curve analysis, although the cut-off value varied slightly. Combining rHA/ vHA/cHA (with any HA≥ the cut-off ) improved the sensitivity from 64-89% to 89-93%, and combining pelvic organ mobility to rHA/ vHA/cHA increased the sensitivity further from 89-93% to 95-97%. Conclusion: Combining levator hiatus area and pelvic organ mobility improves sensitivity of transperineal ultrasound diagnosis of POP, whether as a frontline test to entail POP-Q grading or to monitor the effect of pelvic floor exercising programs.